(untitled) (ModaPalavra e-periódico, 2026)
This article discusses modular patternmaking as a creative system based on the development of interchangeable modules capable of being articulated in multiple ways, enabling distinct product configurations. A responsible design approach is adopted, considering from the early stages of the project aspects related to adaptation, reconfiguration, and reuse. This is an action research study, preceded by exploratory and descriptive research, in which the integration between theoretical framework and experimental practice enables the conception and materialization process of a textile artifact designed under the zero-waste premise and structured from a system of interconnected modules. The study is grounded in the design principles of Nanni Strada and Issey Miyake. The results show that experimentation, as a creative strategy applied to modular patternmaking, emerges as a tool that promotes aesthetic and technical-productive innovation, contributing to resource optimization and the mitigation of environmental impacts arising from the production process.